A statistical model for the demand of undergraduate engineering courses in Portugal : a first study of Bologna Process impact - Oliveira, Raquel (2012)
The observed changes in higher education, at least in the past 12 years, have changed the way students choose the academic program which they wish to attend in higher education, particularly in engineering. In this study, we used regression analysis applied to count data by means a negative binomial model for the access to higher education engeneering programs. The data used consider the academic year 2010/2011 given by Portuguese Ministry of Education. The statistical model obtained presents a statistical significance for the explanatory variables applied.